Large dynamic range microwave photonics mixing system based on parallel DPMZM - Yongsheng GAO; Fangjing SHI; Jiajun TAN; Yangyu FAN (Tongxin xuebao)
To solve the problems of nonlinear distortion and limited dynamic range of microwave photonics mixing system, a large dynamic range microwave photonics mixing system based on parallel dual parallel Mach-Zehnder modulator (DPMZM) was proposed.The parallel modulation of radio frequency and local oscillator signals was realized by using DPMZM.The third-order intermodulation distortion (IMD3) in the output intermediate frequency signal was eliminated by configuring the electro-optic modulation index of the two parallel channels and the working point of the modulators.Finally, the dynamic range of the system was improved.Simulation results show that the proposed scheme can suppress IMD3 by 17.7 dB and increase the SFDR to 127.8<mtext> dB</mtext>· <mtext>Hz</mtext> 4 5 .